1995
DOI: 10.1164/ajrccm.151.5.7735589
|View full text |Cite
|
Sign up to set email alerts
|

Dietary antioxidant vitamin intake and lung function in the general population.

Abstract: We have investigated the relation between lung function and dietary intake of the antioxidant vitamins C and E in the general population in a cross-sectional survey of a random sample of adults from the electoral register of an administrative area of Nottingham. In 2,633 subjects 18 to 70 yr of age, we measured FEV1 and FVC, allergen skin sensitivity to grass pollen, cat fur, and Dermatophagoides pteronyssinus, pack-years smoking exposure by personal recall, and usual dietary intake of vitamins C and E by semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
167
3
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 269 publications
(192 citation statements)
references
References 28 publications
17
167
3
5
Order By: Relevance
“…We have previously reported that FFQ estimates of intake of vitamin C were directly related to FEV 1 in this population (Britton et al, 1995). An association between plasma vitamin C and lung function has also been demonstrated in several other studies (Ness et al, 1996;Hu & Cassano, 2000;Schunemann et al, 2001;Kelly et al, 2003) and is consistent with the hypothesis that increased antioxidant status protects the lungs against loss of lung function.…”
Section: Vitamin Csupporting
confidence: 88%
See 4 more Smart Citations
“…We have previously reported that FFQ estimates of intake of vitamin C were directly related to FEV 1 in this population (Britton et al, 1995). An association between plasma vitamin C and lung function has also been demonstrated in several other studies (Ness et al, 1996;Hu & Cassano, 2000;Schunemann et al, 2001;Kelly et al, 2003) and is consistent with the hypothesis that increased antioxidant status protects the lungs against loss of lung function.…”
Section: Vitamin Csupporting
confidence: 88%
“…The negative finding in relation to vitamin E also corroborates our analysis of data on vitamin E intake in this population (Britton et al, 1995), although the validity of the conclusions based on the analyses of the plasma vitamin E levels is questioned by the fact that we were unable to obtain fasting samples, and do not have estimates of serum cholesterol or triglycerides to adjust for confounding by these variables (Hunter, 1990;Traber & Jialal, 2000). Some (Hu & Cassano, 2000;Schunemann et al, 2001) but not all (Grievink et al, 1999;Grievink et al, 2000) studies have described positive associations between serum vitamin E and lung function, but those that did demonstrate an effect used either fasting samples (Schunemann et al, 2001) or adjusted for serum triglycerides and total cholesterol in their analysis (Hu & Cassano, 2000); and so we are unable to exclude the possibility that our nonfasting samples were insufficient to detect an effect.…”
Section: Vitamin Esupporting
confidence: 88%
See 3 more Smart Citations